Concept development in aspects of ecology - Webb, Paul (Rhodes University, Faculty of Education, Department of Education, 1988)
In this study food webs and a case study are used to investigate concepts which university students and high school pupils hold about ecology and the degree to which concept development has taken place at particular educational levels. The sample was drawn from first year zoology students and biology pupils in standards eight and ten. Present data indicate that students and pupils could solve problems involving the interactions of populations only if they were simple enough to be answered using strategies based on the food chain concept. Very few subjects could succesfully determine all the interacting pathways along which effects may be transmitted within a food web. The ability to determine all the pathways along which the effects of a change in population numbers within a community are spread, and to analyse the possible net manifestation of sometimes conflicting forces, requires a clear understanding of the concept of food web. An immature understanding of the food web concept by the subjects of this study is suggested as, in most cases, they identified alternate pathways within the food web when explicitly asked to do so, but did not apply this strategy when asked to solve problems based on the same principle. The case study also revealed immature ecological concepts. Responses by standard eight pupils indicate that the opportunity exists at this level to develop a clear and mature understanding of the concept of food web, while comparison of data provided by the three age groups suggests that if clear conceptual development regarding food webs does not take place at school, misconceptions are likely to persist among first year university students.
Keywords: Ecology -- Study and teaching